Predictor of academic performance: personality traits and catechol-O-methyltransferase polymorphisms - Salfarina Ramli; Nor Suhaila Rosmimi Rosli; Roziah Mohd Janor; Rohana Ahmad; Lay Kek Teh; Mohd Zaki Salleh; Sahol Hamid Abu Bakar; Richard Johari James (International Journal of Evaluation and Research in Education (IJERE), 2024)
Personality traits and genetics are important factors in determining academic performance. Although there have been studies on the association between genetics and academic performance, there is limited data on the effect of personality traits and the catechol-O-methyltransferase (COMT) rs4680 polymorphism on academic performance, particularly among university students in Malaysia. The objective of this study was to correlate the relationship between personality traits, COMT rs4680 polymorphism, and academic performance among health sciences undergraduate students at a Malaysian university. The research design was a correlational study where 221 students were recruited based on the convenient sampling approach. The demographic and international personality item pool (IPIP) questionnaires were administered online, whereas the COMT rs4680 single nucleotide polymorphism (SNP) was determined using a tetra-primer allele-specific polymerase chain reaction (PCR). From the IPIP results, the conscientiousness trait was positively and significantly correlated with academic performance (r=0.141, p=0.036). Participants with homozygous Met/Met allele of the COMT rs4680 polymorphism tended to perform better in academics (p=0.009) as compared to participants with homozygous Val/Val and heterozygous Val/Met alleles. As a conclusion, students with a higher conscientiousness score and carriers of the homozygous Met/Met allele of COMT rs4680 showed better academic performance.